PEMAKAIAN ALPHA-BISABOLOL DI BIDANG DERMATOLOGI - Intan Fitriyana (Jurnal Medika Hutama, 2022)
Alpha-bisabolol (BISA) is an unsaturated monocyclic sesquiterpene compound with a characteristic floral odor, mainly found in chamomile (Matricaria chamomilla) essential oil which is used in decorative cosmetics, delicate fragrances, shampoos, toilet soaps and other toiletries as well as non-cosmetic products such as household cleaners and detergents. To find out more about the use of Alpha-bisabolol (BISA) in the field of dermatology using the method, namely the study of literature from international journals by summarizing the topic of discussion and comparing the results presented in the article. The use of BISA in the field of dermatology, such as in the cosmetic field, especially in the treatment of anti-aging, hyperpigmentation, whitening effect and antioxidants for the skin. For example, BISA essential oil also contains up to 50% Alpha-bisabolol and this is a molecule that is considered to be the main component that contributes to its anti-inflammatory effect.